EVALUASI KEPUTUSAN DEBT FINANCING PERUSAHAAN GO PUBLIC 1992-1996 - Sukirno DS (LPPM UNY, 2002)
Abstract The sustainability of Indonesian economic crisis happened because of multifaactors. One of those is called non-performing loans that are borned from debt financing done by companies. This research intend to know appropriateness of debt financing decision in go public companies in Indonesia from the stand point of stockholder interest. Research samples were drawn purposively from Indonesia Capital Market Directory 1995 and 1997. Companies selected were published financial statements respectively from 1992 to 1996. Hyphothesis was tested by mean values of debts and losses affected by interest expenses exceed from companies profit. Based on this research analysis can be drawn two main conclusions, that are (1) before economic crisis happened, total of debt financing done by companies was bigger than total of their equity financing, (2) before ecomonic crisis happened, companies pay more interest expenses than profit reported. Based on two relationship conclusions, debt financing decided by management was inappropriate in relation to business continuity concept. Keywords: debt financing, ROI, go public company, BEJ